Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am supposed to find the Maclaurin expantion of

$ \log\left( \frac{1+x}{1-x} \right) $

So I noticed the obvious that $\log(1+x) - \log(1-x)$

Then Maclaurin polynomial of $\log (1+x)$ equals $\sum_{n=0}^{\infty} (-1)^{n+1}\frac{x^n}{n}$

So by doing a quick quick change of variables (-x) I obtained the maclaurin expansion of $\log(1-x)$

In total, I obtained that the Maclaurin expansion of $ \log\left( \frac{1+x}{1-x} \right) $ equals.

$ \displaystyle P(x) = \sum_{n=0}^{\infty} (-1)^{n+1}\frac{x^n}{n} - \sum_{n=0}^{\infty} (-1)^{n+1}\frac{(-x)^n}{n}$

But in my book the answer says $2 \sum_{n=0}^{\infty} \frac{1}{1+2n} x^{2n+1}$, I can see that this is correct, by writing out a few terms. But how do I show this by algebra?

My question is therefore, how do I show that

$\displaystyle \sum_{n=0}^{\infty} (-1)^{n+1}\frac{x^n}{n} - \sum_{n=0}^{\infty} (-1)^{n+1}\frac{(-x)^n}{n} = 2 \sum_{n=0}^{\infty} \frac{1}{1+2n} x^{2n+1}$


share|cite|improve this question
Use $\log(1+x) = \log(1-(-x))$ and expand around $x=0$ just as you did for $\log(1-x)$. – Sasha Mar 6 '12 at 14:54
But I have already done this note the $x-2$ – N3buchadnezzar Mar 6 '12 at 14:55
$1+x$ becomes $1+x-2 = x-1 $ after replacing $x$ with $x-2$, not $1-x$ as required. To make $1+x$ become $1-x$, replace $x$ everywhere with $-x.$ – Ragib Zaman Mar 6 '12 at 14:58
Where did you get $x-2$ from? – Ilya Mar 6 '12 at 14:58
Silly mistake! I will fix it now – N3buchadnezzar Mar 6 '12 at 15:01
up vote 3 down vote accepted

The expansion for $\log (1+x)$ is not $\sum_{n=0}^{\infty} (-1)^{n+1}\frac{x^n}{n}$, but $$\begin{equation*} \log (1+x)=\sum_{n=0}^{\infty }\frac{\left( -1\right) ^{n}}{n+1}% x^{n+1}=\sum_{n=1}^{\infty }\frac{\left( -1\right) ^{n+1}}{n}x^{n+1} \end{equation*}.$$


$$ \begin{eqnarray*} \log (1-x) &=&\sum_{n=0}^{\infty }\frac{\left( -1\right) ^{n}}{n+1}\left( -x\right) ^{n+1}=\sum_{n=0}^{\infty }\frac{\left( -1\right) ^{n}\left( -1\right) ^{n+1}}{n+1}x^{n+1} \\ &=&-\sum_{n=0}^{\infty }\frac{1}{n+1}x^{n+1}, \end{eqnarray*} $$

and $$ \begin{eqnarray*} \log \left( \frac{1+x}{1-x}\right) &=&\log (1+x)-\log (1-x) \\ &=&\sum_{n=0}^{\infty }\frac{\left( -1\right) ^{n}}{n+1}x^{n+1}+\sum_{n=0}^{ \infty }\frac{1}{n+1}x^{n+1} \\ &=&\sum_{n=0}^{\infty }\frac{\left( -1\right) ^{n}+1}{n+1}x^{n+1} \\ &=&\sum_{n=0}^{\infty }\frac{2}{2n+1}x^{2n+1}, \end{eqnarray*}$$

because $$ \begin{equation*} \left( -1\right) ^{n}+1=\left\{ \begin{array}{c} 2\quad \text{if }n\text{ even} \\ 0\quad \text{if }n\text{ odd}. \end{array} \right. \end{equation*}$$

share|cite|improve this answer

It makes :

${\displaystyle \sum_{n=1}^{\infty}(-1)^{n+1}\dfrac{x^{n}}{n}}-(-1)^{n+1+n}\dfrac{x^{n}}{n}={\displaystyle \sum_{n=1}^{\infty}(-1)^{n+1}\dfrac{x^{n}}{n}}+\dfrac{x^{n}}{n}={\displaystyle \sum_{n=0}^{\infty}\dfrac{2x^{n}}{2n+1}}+{\displaystyle \sum_{n=1}^{\infty}-\dfrac{x^{n}}{2n}+\dfrac{x^{n}}{2n}}={\displaystyle \sum_{n=0}^{\infty}\dfrac{2x^{n}}{2n+1}}$

share|cite|improve this answer
What did you do from 2 to 3 ? – N3buchadnezzar Mar 6 '12 at 15:28
I'm french, so I hope that it will be "understandable". I separated the even and odd terms. – matovitch Mar 6 '12 at 15:32

In fact you have $ (-1)^{n+1} (-x)^n = -(x)^n$. Thus if you look the term of the two sum you have: $x^n\frac{1 - (-1)^{n}}{n}$ and for the complete sum : $2\sum_{k .odd} \frac{x^k}{k}$ it's exactly that you want.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.